Rethinking Obligation A Feminist Method for Political Theory - Hirschmann, Nancy J. (Cornell University Press, 1992)
In Rethinking Obligation, Nancy J. Hirschmann provides an innovative analysis of liberal obligation theory that uses feminism as a theoretical method for rethinking political obligations from the bottom up. In articulating a feminist method for political theory, Hirschmann skillfully brings together theoretical categories and methods previously seen as opposed: feminist standpoint and postmodernism, gender psychology and anti-essentialism, empiricism and interpretivism. Rethinking Obligation mounts a vital challenge to central aspects of liberal theory. Students and scholars of political philosophy, political theory, feminist theory, and women's studies will want to read it.